(3fXe GdeYdheGJ GdGOGQjIs - (3aGjR LeYg UGdM(B, (3GdfLGQs ((3YeGf(B:s (3OGQ GdMGeO ddfTQ h GdJhRjY(B,s, 2007)
(3jJfGhd gPG GdcJGH eGjdj fXe GdeYdheGJ GdGOGQjI (B: (3JGdeaghe hGdWHjYI , fXe GdeYdheGJ hGdefXeGJ , GdfXe ef efXhQ hXjaj , fXe GdESfGO GdEOGQjI , bhGYO GdHjGfGJ , GdGJUGdGJ hGdTHcGJ , Cef GdeYdheGJ hGdeSDhdjGJ GdCNdGbjI hGdGLJeGYjI , GdJNWjW GdGSJQGJjLj dfXe GdeYdheGJ GdEOGQjI , efgLjI JWhjQ fXe GdeYdheGJ GdGOGQjI fXe GdeYdheGJ aj YUQ GdYhdeIs
(3HjHdjhZQGajG U(B.359 (3edGMb U(B.371s
Keywords: (3GOGQI GdGYeGds; (3GdeYdheGJ GdGOGQjIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s